Optimisation of asarone removal from Piper sarmentosum Roxburgh leaves using supercritical carbon dioxide extraction: the Box-Behnken design - Mohd Shahrul Ridzuan Hamil; Nornisah Mohamed; Zhari Ismail (Universidade de São Paulo, 2022)
Abstract Piper sarmentosum is a herbaceous shrub with numerous pharmacological benefits. However, the presence of two toxic phenylpropanoids (α- and β-asarone) limits the medicinal usage of the plant. In this study, the extraction of three asarone isomers, namely α-, β-, and -asarone was optimised using supercritical carbon dioxide extraction (SC-CO2) combined with Box-Behnken experimental design. Comparison of asarone contents in different conventional solvent extracts of P. sarmentosum leaves prior to and after SC-CO2 extraction was performed. The SC-CO2 method successfully maximised the extraction of α-, β-, and ɣ-asarone at P = 81.16 bar, T = 50.11°C, and t = 80.90 min, yielding 13.91% α-asarone, 3.43% β-asarone, and 14.95% ɣ-asarone. The SC-CO2 residue of the leaves re-extracted with conventional solvents showed a significant decrease of asarone ranging from 45% to 100% (p<0.001) compared to their counterparts without SC-CO2 treatment. α-, β-, and ɣ-asarone were completely removed in the ethanol extract of the residue. These findings suggested that the optimised SC-CO2 extraction parameters may serve as a quick treatment step for the selective removal of asarone from P. sarmentosum to develop safer extracts for the food and nutraceutical industries applications.